Effect of Fusarium virguliforme phytotoxin on soybean gene expression suggests a role in multidimensional defence. (13th December 2012) - Radwan, Osman; Li, Min; Calla, Bernarda; Li, Shuxian; Hartman, Glen L.; Clough, Steven J.
Summary: Sudden death syndrome (SDS), caused by Fusarium virguliforme, is an important yield‐limiting disease of soybean. This soil‐borne fungus colonizes soybean roots causing root rot, and also releases a phytotoxin that is translocated to leaves causing interveinal chlorosis and necrosis leading to defoliation and early maturation. The objective of our study was to compare gene expression profiles during the early response of soybean leaves exposed to sterile culture filtrates of F. virguliforme in soybean genotypes with different levels of resistance to SDS. The analysis identified SDS‐related defence genes that were induced in the most resistant genotype, but not in the other genotypes. Further functional annotations based on sequence homology suggested that some of the induced genes probably encode proteins involved in cell wall modification, detoxification, defence responses, primary metabolism and membrane transport. Quantitative real‐time reverse‐transcribed polymerase chain reaction confirmed the differential transcript accumulation of a subset of these genes. In addition, in silico mapping of differentially expressed genes to SDS‐resistant quantitative trait loci allowed for the identification of new potential defence genes that could be genetically mapped to the soybean genome, and could be used further in a marker‐assisted selection programme. A comparison of the response of soybean to F. virguliforme phytotoxin ( Fv toxin) relative to other biotic and abiotic stresses revealed that the resistance response to Fv toxin is quite similar to the response to inoculation with an incompatible Pseudomonas syringae pv. glycinea strain, suggesting that Fv toxin might induce hypersensitive response pathways in soybean leaf tissues in the absence of pathogen in these tissues.